Hiding Processing Approaches For Digital Images Encryption Using Wavelet Transform - Younis, Hameed A.; Abdalla, Turki Y.; Abdalla, Abdulkareem Y. (Basrah Journal for Engineering Sciences, 2008)
The use of image communication has increased in recent years. In this approach, the encryption process is performed by hiding the processing steps of the wavelet transform. The attacker cannot obtain the original image unless processing steps are known. In this paper, the performance of three different hidden wavelet-based schemes are applied. First, hiding filter types encryption scheme (HFT), second, hiding wavelet packet tree encryption scheme (HWPT), lastly, by combining the previous two methods (HFTWPT). Several experiments are given to illustrate the performance of the proposed schemes.